2003
DOI: 10.1046/j.1469-0691.2003.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of pleural fluid anti-A60 IgM in BCG-vaccinated tuberculous pleurisy patients

Abstract: We suggest that in populations where tuberculosis prevalence is high and BCG vaccination is common, pleural fluid anti-A60 IgM can facilitate the diagnosis of TP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…Kunter et al, after evaluating IgM anti-A60 in PF, reported similar sensitivity (77%) and specificity (94%) (17). However, when the combined results of all dilutions were analyzed, the sensitivity was higher (Ն80%) than that obtained in the histopathological biopsy examinations (74%), which in this particular case is a decided advantage.…”
Section: Discussionmentioning
confidence: 82%
“…Kunter et al, after evaluating IgM anti-A60 in PF, reported similar sensitivity (77%) and specificity (94%) (17). However, when the combined results of all dilutions were analyzed, the sensitivity was higher (Ն80%) than that obtained in the histopathological biopsy examinations (74%), which in this particular case is a decided advantage.…”
Section: Discussionmentioning
confidence: 82%
“…Sample sizes in the three studies were between 81 206 and 125 207 and TB prevalence ranged from 56% 208 to 70%. 207 The commercial tests (ICT, 208 Anda TB IgG 207 and Anda TB IgM 207 ) were each evaluated in serum and in pleural fluid samples. The in-house test evaluation 206 was carried out with pleural fluid samples only.…”
Section: Anti-tb Antibody Testsmentioning
confidence: 99%
“…Among pleural fluid antibody tests, detection of IgA against MPT-64 and MT-10.3 (Rv3019c), two recombinant protein antigens, had the best sensitivity [20,40]. Anti-A60 IgM and IgG antibodies in pleural fluid had suboptimal sensitivity for TB [41]. Using antibodies against five different antigens, CHIERAKUL et al [42] found the performance of serology of pleural fluid to be disappointing, with sensitivity and specificity ,60%.…”
Section: B-cell Response (Antibody Detection)mentioning
confidence: 99%